output.to from Sideway
Draft for Information Only

# Content

`Algebra Factors  Factoring Special Binomials  Factoring Special Polynomials   Binomal Factors of Special Polynomials   Polynomal Factors of Special Polynomials   Powers of Binomials   Powers of Polynomial Sources and References`

# Algebra

## Factors

### Factoring Special Binomials

Some typical binomial factoring are 𝑎2−𝑏2=(𝑎−𝑏)(𝑎+𝑏) 𝑎3−𝑏3=(𝑎−𝑏)(𝑎2+𝑎𝑏+𝑏2) 𝑎3−𝑏3=(𝑎+𝑏)(𝑎2−𝑎𝑏+𝑏2) In general, 𝑎𝑛−𝑏𝑛=(𝑎−𝑏)(𝑎𝑛−1+𝑎𝑛−2𝑏+⋯+𝑏𝑛−1) Or, if 𝑛 is even 𝑎𝑛−𝑏𝑛=(𝑎+𝑏)(𝑎𝑛−1−𝑎𝑛−2𝑏+⋯−𝑏𝑛−1) And only if 𝑛 is odd. 𝑎𝑛+𝑏𝑛=(𝑎+𝑏)(𝑎𝑛−1−𝑎𝑛−2𝑏+⋯−𝑏𝑛−1)

### Factoring Special Polynomials

#### Binomal Factors of Special Polynomials

Typical polynomials from special factors (𝑥+𝑎)(𝑥+𝑏)=𝑥2+(𝑎+𝑏)𝑥+𝑎𝑏 (𝑥+𝑎)(𝑥+𝑏)(𝑥+𝑐)=𝑥3+(𝑎+𝑏+𝑐)𝑥2+(𝑏𝑐+𝑐𝑎+𝑎𝑏)𝑥+𝑎𝑏𝑐

#### Polynomal Factors of Special Polynomials

𝑎4+𝑎2𝑏2+𝑏4=(𝑎2+𝑎𝑏+𝑏2)(𝑎2−𝑎𝑏+𝑏2) 𝑎4+𝑏4=(𝑎2+𝑎𝑏√2+𝑏2)(𝑎2−𝑎𝑏√2+𝑏2) 𝑎2+𝑏2−𝑐2+2𝑎𝑏=(𝑎+𝑏)2−𝑐2=(𝑎+𝑏+𝑐)(𝑎+𝑏−𝑐) 𝑎2−𝑏2−𝑐2+2𝑏𝑐=𝑎2−(𝑏−𝑐)2=(𝑎+𝑏+𝑐)(𝑎−𝑏+𝑐) 𝑎3+𝑏3+𝑐3-3𝑎𝑏𝑐=(𝑎+𝑏+𝑐)(𝑎2+𝑏2+𝑐2−𝑏𝑐−𝑐𝑎−𝑎𝑏) 𝑏𝑐2+𝑏2𝑐+𝑐𝑎2+𝑐2𝑎+𝑎𝑏2+𝑎2𝑏+𝑎3+𝑏3+𝑐3=(𝑎+𝑏+𝑐)(𝑎2+𝑏2+𝑐2) 𝑏𝑐2+𝑏2𝑐+𝑐𝑎2+𝑐2𝑎+𝑎𝑏2+𝑎2𝑏+3𝑎𝑏𝑐=(𝑎+𝑏+𝑐)(𝑏𝑐+𝑐𝑎+𝑎𝑏) 𝑏𝑐2+𝑏2𝑐+𝑐𝑎2+𝑐2𝑎+𝑎𝑏2+𝑎2𝑏+2𝑎𝑏𝑐=(𝑏+𝑐)(𝑐+𝑎)(𝑎+𝑏) 𝑏𝑐2+𝑏2𝑐+𝑐𝑎2+𝑐2𝑎+𝑎𝑏2+𝑎2𝑏−2𝑎𝑏𝑐−𝑎3−𝑏3−𝑐3=(𝑏+𝑐−𝑎)(𝑐+𝑎−𝑏)(𝑎+𝑏−𝑐) 𝑏𝑐2−𝑏2𝑐+𝑐𝑎2−𝑐2𝑎+𝑎𝑏2−𝑎2𝑏=(𝑏−𝑐)(𝑐−𝑎)(𝑎−𝑏) 2𝑏2𝑐2+2𝑐2𝑎2+2𝑎2𝑏2−𝑎4−𝑏4−𝑐4=(𝑎+𝑏+𝑐)(𝑏+𝑐−𝑎)(𝑐+𝑎−𝑏)(𝑎+𝑏−𝑐) 𝑥3+2𝑥2𝑦+2𝑥𝑦2+𝑦3=(𝑥+𝑦)(𝑥2+𝑥𝑦+𝑦2) In general, (𝑥+𝑦)𝑛−(𝑥𝑛+𝑦𝑛) is divided by 𝑥2+𝑥𝑦+𝑦2

#### Powers of Binomials

Some typical polynomals from powers of binomials: (𝑎+𝑏)2=𝑎2+2𝑎𝑏+𝑏2 (𝑎−𝑏)2=𝑎2−2𝑎𝑏+𝑏2 (𝑎+𝑏)3=𝑎3+3𝑎2𝑏+3𝑎𝑏2+𝑏3=𝑎3+𝑏3+3𝑎𝑏(𝑎+𝑏) (𝑎−𝑏)3=𝑎3−3𝑎2𝑏+3𝑎𝑏2−𝑏3=𝑎3−𝑏3−3𝑎𝑏(𝑎+𝑏) Similarly, 𝑥+1𝑥2=𝑥2+2+1𝑥2=𝑥2+1𝑥2+2 𝑥+1𝑥3=𝑥3+3𝑥+1𝑥+1𝑥3=𝑥3+1𝑥3+3𝑥+1𝑥 And Generally, for example 𝑛=7, (𝑎±𝑏)7=𝑎7±7𝑎6𝑏+21𝑎5𝑏2±35𝑎4𝑏3+35𝑎3𝑏4±21𝑎2𝑏5+7𝑎1𝑏6±𝑏7 The next coefficients can be determined by Newton's Rule: Multiply any coefficient by the index ofthe leading quantity, and divide by the number of terms to that plcact to obtain the coefficient of the term next following. i.e. 35=21×5÷3=35×4÷4.

#### Powers of Polynomial

Some typical polynomials from powers of polynomials: (𝑎+𝑏+𝑐+𝑑)2=𝑎2+2𝑎(𝑏+𝑐+𝑑)+𝑏2+2𝑏(𝑐+𝑑)+𝑐2+2𝑐𝑑+𝑑2  =𝑎2+𝑏2+𝑐2+𝑑2+2𝑎(𝑏+𝑐+𝑑)+2𝑏(𝑐+𝑑)+2𝑐𝑑 (𝑎+𝑏+𝑐)2=𝑎2+𝑏2+𝑐2+2𝑏𝑐+2𝑐𝑎+2𝑎𝑏 (𝑎+𝑏+𝑐)3=𝑎3+𝑏3+𝑐3+3(𝑏2𝑐+𝑏𝑐2+𝑐2𝑎+𝑐𝑎2+𝑎2𝑏+𝑎𝑏2)+6𝑎𝑏 In an algebraical equation, the sign of any letter may be changed throughout, and thus a new formula obtained by keeping an even power of a negative quantity is positive. (𝑎+𝑏−𝑐)2=𝑎2+𝑏2+𝑐2−2𝑏𝑐−2𝑐𝑎+2𝑎𝑏

## Sources and References

https://archive.org/details/synopsis-of-elementary-results-in-pure-and-applied-mathematics-pdfdrive

ID: 210500028 Last Updated: 5/28/2021 Revision: 0 Ref:

References

1. B. Joseph, 1978, University Mathematics: A Textbook for Students of Science &amp; Engineering
2. Wheatstone, C., 1854, On the Formation of Powers from Arithmetical Progressions
3. Stroud, K.A., 2001, Engineering Mathematics
4. Coolidge, J.L., 1949, The Story of The Binomial Theorem

Nu Html Checker 53 na na

Home 5

Management

HBR 3

Information

Recreation

Culture

Chinese 1097

English 339

Computer

Hardware 224

Software

Application 213

Latex 52

Manim 204

KB 1

Numeric 19

Programming

Web 289

Unicode 504

HTML 66

CSS 65

SVG 46

ASP.NET 270

OS 429

Python 72

Knowledge

Mathematics

Algebra 84

Geometry 33

Calculus 67

Engineering

Mechanical

Rigid Bodies

Statics 92

Dynamics 37

Control

Natural Sciences

Electric 27